The Simple Past Tense - Ramírez-Castro, Monserrat (My University, 2019)
Infografía sobre uso del pasado.

Past tense infographic
Keywords: Pasado simple; Past tense; Pronunciación; Pronunciation; -ed endings; Inglés; English